Cutaneous bronchogenic cyst over sternum: A rare case report - Singh, Smita; Kashyap, Anamika; Agarwal, Kiran; Sailo, Lalrinzuali (Indian Journal of Case Reports, 2017)
Bronchogenic cyst is a congenital developmental abnormality of the embryonic foregut and is found most commonly in the mediastinum with rare occurrence on the skin or subcutaneous tissues. We report a case of cutaneous bronchogenic cyst that occurred in the skin over the sternum in a 24-year-old male. On ultrasonography, a well-circumscribed, non-echogenic cystic mass was observed measuring 2 cm × 2 cm. Histologically, the cyst was lined by ciliated, pseudostratified, columnar epithelium with interspersed goblet cells, and there were bundles of smooth muscle fibers in the cyst wall. Cutaneous bronchogenic cysts are uncommon congenital malformations and should be included in the differential diagnosis of congenital cystic and nodular skin lesions on the upper chest, upper back, and neck.